Analysis on the Writing Errors of Grade 6 Students: Basis for Instructional Material Development - Mylen H. Dejon; Evangeline H. Alvarez; Roxan R. Remorosa; Shiryl T. Ytoc (RIRAI Publisher, 2024)
The ability of students to express themselves through writing is not just a reflection of their linguistic prowess but also a determinant of their academic and future career success. The purpose of this study is to conduct an analysis on the writing errors of Grade 6 students of Paciencia Elementary School, Loreto, Agusan Del Sur. The findings would be used as the basis for instructional material development and to recommend emphasizing teaching integration of the identified errors. The dominant errors were related to punctuation, capitalization, and incorrect verb forms, indicating a significant need for focused instruction in these areas to improve pupils' writing proficiency. In response to these findings, the study suggests developing targeted instructional materials that include structured lessons and practice exercises focusing on the most common errors. These resources should be integrated into the curriculum. Recommendations from the study emphasize the roles of various stakeholders in improving writing skills among pupils. Teachers should implement targeted instructional materials and attend professional development workshops. The school administration should support the integration of these materials and fund workshops while regularly assessing pupils' grammar skills. Pupils should engage actively in grammar lessons and seek feedback, and parents should encourage and support their children in practicing grammar skills at home. Policymakers and curriculum developers should incorporate the study's findings into national curriculum standards and allocate resources to support these initiatives. Future research should explore additional factors affecting grammar skills and the long-term impact of targeted instruction on overall academic performance.